A case report of synovial sarcoma arising in the abdominal wall muscles - Wen-Xu Liu; Wen-Qian Liu; Ji-Guang Song; Ming-Hao Jia; Jia-Le Wang; Feng-Ling Li; Jia-You Xu (Medicine, 2026)
Rationale: Synovial sarcoma, a rare form of soft tissue sarcoma, typically manifests in the synovium of major joints. The incidence of this disease in the intermuscular region of the abdominal wall, as observed in this particular case, is an even rarer occurrence. Relying solely on conventional imaging modalities often proves insufficient for establishing a definitive diagnosis. Patient concerns: A 67-year-old female inadvertently palpated a mass in the abdomen two years ago. The mass was firm in texture and had limited mobility. The patient expressed concerns regarding the possibility of it being a malignant tumor. Diagnoses: Prior to the operation, color-Doppler ultrasonography of the local superficial mass revealed a hypoechoic area measuring 2.2 × 1.2 × 2.6 cm within the muscular layer at the site on the left abdominal wall as described by the patient. The lesion exhibited a distinct border, an irregular morphology, heterogeneous internal echoes, and a small amount of blood flow signals. postoperative pathological examination confirmed the diagnosis of synovial sarcoma. Interventions: Surgical treatment was performed, followed by 4 cycles of chemotherapy post-operation. Outcomes: Complete resection was accomplished. postoperative computed tomography (CT) reevaluation of the patient demonstrated no evidence of metastasis. Lessons: For suspicious masses in unconventional locations, systematic examinations should be conducted as soon as possible, including imaging tests and preoperative pathological biopsy, in order to reduce the rate of preoperative misdiagnosis and missed diagnoses. Early diagnosis will minimize the risks and losses for the patient.